A Rare Case of Fatal Self-Poisoning With Sodium Nitrite: Autopsy and Toxicological Findings. (December 2021) - Barranco, Rosario; Frigiolini, Francesca Maria Elena; Orcioni, Giulio Fraternali; Malandrino, Mery; Salomone, Alberto; Ventura, Francesco
Abstract : Abstract: Fatal sodium nitrite poisonings are unusual in the forensic setting. Suicide by poisoning includes drug overdose, the inhalation of toxic gasses, and poisoning from pesticides and chemical substances. Sodium nitrite is an inorganic compound usually seen as a crystalline powder that is very water soluble. Sodium nitrite is used mostly in the food industry (as a preservative) and in medical field (as an antidote to cyanide poisoning), and if ingested in large enough amounts, it can be fatal. The ingestion of sodium nitrite can cause severe methemoglobinemia, which is a metabolic disorder characterized by an inability of hemoglobin (which gets oxidized into methemoglobin) to bind (and therefore carry) oxygen. Severe cases of this condition, if not treated, can be fatal. We describe a case of fatal self-poisoning with sodium nitrite; in particular, the article focuses on the autoptic and toxicological investigations that enabled the correct diagnosis to be established.